THE BEGINNING OF ARTIFICIAL INTELLIGENCE - Kurbanova Madina Rustam kizi (Web of Journals Publishing, 2024)
The article formulates the main goals and objectives of artificial intelligence. It is shown how AI is related to the development of world computer science. A brief history is also presented about the outstanding scientists who stood at the origins of cybernetics, computer science and artificial intelligence, as well as the prospects for its further development.
Keywords: computer science, cybernetics, computers, artificial intelligence.